2022
DOI: 10.3389/fpsyg.2022.1015441
|View full text |Cite
|
Sign up to set email alerts
|

The influencing factors of individual interest in physical education based on decision tree model: A cross-sectional study

Abstract: To identify the key influencing factors and analyze the internal relationship among the factors of individual interest in PE, we conducted a cross-sectional survey of a large sample of Chinese young students based on the decision tree model. A total of 3,640 young students (Mage = 14.16; 7–18 years; SD = 2.66, 47% boys) were investigated by using six questionnaires, including individual interest in physical PE, self-efficacy, achievement goals, expectancy value in PE, PE knowledge and skills and PE learning en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…The questionnaire consisted of 16 randomly arranged items rated on a five‐point Likert scale (1 = very bad to 5 = very good). Lin and Zhu (2022) confirmed the questionnaire's reliability and construct validity, and results indicated that this questionnaire could be used.…”
Section: Methodsmentioning
confidence: 84%
See 4 more Smart Citations
“…The questionnaire consisted of 16 randomly arranged items rated on a five‐point Likert scale (1 = very bad to 5 = very good). Lin and Zhu (2022) confirmed the questionnaire's reliability and construct validity, and results indicated that this questionnaire could be used.…”
Section: Methodsmentioning
confidence: 84%
“…The 12 items were randomly arranged and rated on a five‐point Likert scale (1 = strongly disagree to 5 = strongly agree). The internal consistency (Cronbach's alpha) and test‐retest reliability results were 0.89 and 0.88, respectively (Lin & Zhu, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations